Analisis Kualitas Pelayanan Kesehatan di Puskesmas Tipar Kota Sukabumi - Muhammad Malik Fajar; Rizki Hegia Sampurna; M. Rijal Amirulloh (Jayapangus Press, 2026)
This study was motivated by several problems identified in the delivery of healthcare services at Tipar Community Health Center, Citamiang District, Sukabumi City. The study aimed to analyze service quality based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This study employed a qualitative approach with a descriptive method. Data were collected through semi-structured interviews, overt and covert observations, and documentation. Informants were selected using purposive and snowball sampling techniques, with five key informants initially chosen through purposive sampling. The results showed that the tangible dimension had not been effectively implemented because the available facilities, infrastructure, and service environment did not fully support patients’ needs. The reliability dimension was considered good, particularly in terms of the accuracy and ability of healthcare personnel to provide services in accordance with established procedures. The responsiveness dimension was categorized as fairly good, although the speed of responding to patients’ needs and complaints still required improvement. The assurance dimension was also considered fairly good because healthcare personnel were able to provide patients with a sense of security, certainty, and trust, although its consistency remained suboptimal. Meanwhile, the empathy dimension was fairly good, as reflected in the personnel’s friendliness, attentiveness, and willingness to understand patients’ needs. These findings indicate that the main strength of the service lies in the reliability of healthcare personnel, while its primary weaknesses concern physical facilities, response speed, and service consistency. Therefore, the quality of healthcare services at Tipar Community Health Center has not yet reached an optimal level. Improvements are particularly required in service facilities, responsiveness, assurance consistency, and individualized attention to patients to create more effective, comfortable, and community-oriented healthcare services.